Perancangan Dashboard Harga Pangan Di Pulau Jawa - Wiyangga Oktaviano; Tri Sutrisno; Irvan Lewenusa (Jurnal Pendidikan, Sains Dan Teknologi, 2025)
This study aims to design an interactive dashboard for monitoring and analyzing food prices in Java Island. The dashboard is developed to display real-time information on key food commodity prices, sourced from reliable data providers such as the National Strategic Food Price Information Center (PIHPS). The primary goal is to facilitate information access for the government and the public, enabling more effective decision-making in response to food price fluctuations. The interactive visualization allows users to track trends, identify distribution issues, and predict price changes. This research employs a quantitative approach to analyze price trends and patterns, utilizing Microsoft Power BI for data visualization. Thus, the dashboard is expected to support better decision-making to maintain economic stability and food security in the region.